Filsafat Keadilan Bermartabat Dalam Hukum Islam: Anatomi Hak Waris Dalam Prinsip Sapikul Sagendhongan - Disantara, Fradhana Putra; neny, Neny rahmawati (Faculty of Shariah UIN Ponorogo, 2024)
Abstract : This research aims to analyze the principles of Islamic inheritance law and their relevance to customary law in society as well as the existence of distribution of inheritance based on the Sapikul Sagendhongan principle from an Islamic Law perspective. This research is normative legal research by prioritizing conceptual and statutory approaches. The results of the research confirm that there are eleven principles or principles in Islamic inheritance law which include: the principle of ijbari', bilateral, individual, balance, solely due to death, sincerity, self-servity, huququl maliyah or material rights, basic rights (huququn thaba 'iyah), dividing inheritance and benefit, where these eleven principles or principles are the basis for the implementation and regulation of Islamic inheritance law. In connection with the application of customary law practices in the distribution of inheritance, it can actually be seen from the theory of receptio in complex which was initiated by Van Den Berg, the theory of receptio exit which was developed by Hazairin, and the theory of receptio a contrario which was developed by Sayuti Talib which is actually a justification that Islamic law has validity. which sometimes manifests itself in customary law, such as the principle of Sapikul Sagendhongan as implemented by Javanese society. The existence of distribution of inheritance based on the Sapikul Sagendhongan principle viewed from the perspective of Islamic Law is actually no different from the distribution of inheritance in Islamic Law which mandates that men share more than women with the argument that men have greater responsibility. In this context, the distribution of inheritance based on the principle of sapikul sagendhongan actually has similarities with the distribution of inheritance based on Islamic law.